Systemic Thinking for Strengthening Teacher Education at the Syekh Abdurrauf Aceh Singkil Islamic College - Neliwati; Muhammad Saripuddin B; Andika Novriadi Cibro (EDUTEC : Journal of Education And Technology, 2023)
The purpose of this study is to discuss Systemic Thinking for Strengthening Teacher Education at the Syekh Abdurrauf Aceh Singkil Islamic College. The method used in this article is qualitative. The results of this study can be concluded that education is a well-planned and well-organized program. A program with several components that work together in a process to achieve a programmed goal. There is an orderly pattern of thinking about finding and seeing things and working as a system. At STAI Abdur Rauf Aceh Singkil in strengthening teacher education by conducting a SWOT analysis and compiling a strategic plan, with SWOT analysis at STAI Syekh Abdurrauf Aceh Singkil, it will be possible to determine the steps in improving teacher education